Wielojęzyczność kłótni -poszukiwanie uniwersalności wzorca gatunkowego (na przykładzie tekstów potocznych, literackich i muzycznych) - Biłas, Ewa; Sujkowska, Katarzyna (Stylistyka, 2021)
This article is a trial of indication of quarrel features ( quarrel as one of speech genres) Features so universal as possible to be found, both in spontaneous, colloquial conversation and also in consciously created, literary and musical texts. Analyse of the same genre in various codes of communication, proved that it is recognizable thanks to existence ofparticular genre indexes which assume various forms according to chosen lingual matter. Undoubtedly common, colloquial quarrel is the main genre. However literally and musical quarrels (as secondary genres), take relevant characteristics of the main genre (structure, intention, configuration of prosody and intonation), while elements of semantic level are modified.